The Construction of Chinese Indonesians in Ngenest Film - Yoel Christian (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
The thesis focuses on how Chinese Indonesians are constructed in Ngenest and why they are constructed that way. Chinese Indonesians become a scapegoat and considered bad ethnic group since they are the minority. By using the Ethnic Construction and Stereotype theory it helps me to reveal the constructions of Chinese Indonesians in Ngenest, and also why they are constructed that way. I would analyze the Chinese Indonesian major and minor characters in Ngenest. This can be revealed from the way they interact with the society in Ngenest. In conclusion, Chinese Indonesians are not accepted as one’s own in their land because of their construction as perpetual foreigners, being loyal to Chinese traditions which makes them different from the rest of the Indonesian society, and being rich by exploiting non-Chinese Indonesians. Since the Chinese Indonesians are the minority, they become a scapegoat and target of non-Chinese Indonesians in the society. Keywords: racism, ethnic construction, stereotyping, representation, Chinese Indonesians